Current Trends in Research into the Utilisation of Wood - Narayanamurti, D. (Indian Forester, 1959)
The Paper points out the countinued need for wood and timber production for the world's economy inspite of the likelihood of its being "eliminated from the structural and energy fields." It puts in a plea for pure research, though there may be a time-lag between a fundamental discovery and its application. The need for continuing research towards improved utilisation of wood, production of wood products and the manufacture of composition products from wood waste, is emphasised.